Dampak Qanun Aceh Nomor 11 Tahun 2018 Tentang Lembaga Keuangan Syari’ah terhadap Bank Konvensional di Aceh - Zulfiyanda (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
Aceh Qanun Number 11 of 2018 on Sharia Financial Institutions requires all financial institutions in Aceh to operate under sharia principles, resulting in the complete cessation of conventional banking services in the province by 2021. This study, using a normative juridical method, examines the legal, economic, and social impacts of the Qanun. The findings show that the regulation reinforces Aceh’s authority to implement Islamic law, but also brings significant economic adjustments, including reduced banking competition, changes in access to financial services, and substantial transition costs. Socially, it reshapes community financial practices and affects the employment of conventional bank workers. The study concludes that the effectiveness of the Qanun depends on the readiness of sharia-based financial infrastructure and policy synchronization between Aceh and national regulators.